PENGARUH PENAMBAHAN EKSTRAK BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP KARAKTERISTIK FISIK, MASA SIMPAN, DAN ORGANOLEPTIK PERMEN JELLY DAUN KERSEN - Veni Rori Setiawati; Puspita Sari (Universitas Muhammadiyah Mataram, 2020)
Jelly is a candy made from components of water or fruit juice, flavor, sugar, and gelling ingredients. Apart from fruit juice, jelly candy can be made from the basic ingredients of leaf extracts. One of the leaves that can be used is Muntingia calabura L. leaves. The existing jelly candies generally do not use natural ingredients as colorings and flavors. Fruits that can be used as natural ingredients in making jelly candy are Averrhoa bilimbi L. This study aims to determine the effect of adding starfruit extract to the physical quality, shelf life, and organoleptic of Muntingia calabura L. leaves jelly candy. This study used a Completely Randomized Design (CRD) with 1 factor, namely the concentration of Averrhoa bilimbi L extract (0%, 5%, 10%, 15%, and 20%). The results of this study indicate that the addition of Averrhoa bilimbi L extract does not significantly affect the physical quality (color) of Muntingia calabura L. leaves jelly candy. In the shelf life test, the addition of Averrhoa bilimbi L extract gave a real effect, where the best treatment was the concentration of Averrhoa bilimbi L. extract 15% and 20%. In the organoleptic test, the addition of Averrhoa bilimbi L extract did not significantly affect the level of preference (hedonic) and the level of acceptance (scoring) of the texture, but it did affect the level of panelist acceptance of the color, aroma, and taste of Muntingia calabura L. leaves jelly candy. The best treatment of panelist acceptance level for color is at a concentration of 0% producing jelly candy with a yellowish-brown color and the best aroma and taste of jelly candy at a concentration of 20% producing jelly Averrhoa bilimbi L -flavored jelly candy with a slightly bitter sweet taste with a slightly bitter sweetness.